School abandonment in the Education of Youth and Adults at Abraham Lincoln School, Medicilândia, Pará (Research, Society and Development, 2022)
The objective is to analyze the aspects related to school dropout in the Youth and Adult Education Program (EJA) at Abraham Lincoln School, Medicilândia, Pará, from 2003 to 2017, analyzing the causes of dropout and the pedagogical difficulties pointed out by teachers and managers educational. This is a quali-quantitative research, in which students, teachers and managers of this teaching unit were interviewed and the final reports of the Youth and Adult Education classes were analyzed during this period. It was found that of the 5670 enrolled in the period 2003 to 2017, 2696 students dropped out of studies, that is, school dropout reached 47.5% over 15 years, with the highest dropout rate being in 2004, with 66.5 %, represented by three hundred and two students who dropped out, also highlighting the years 2006, 2012, 2014 and 2015. It was found that the most common causes of students residing in urban areas is the difficulty of reconciling with work and the low motivation of the students. and those in rural areas, in addition to work, the lack of regular public transport to travel to the city was mentioned. Another critical point for students' learning and permanence is the lack of didactic and pedagogical support, and the use of non-differentiated methodologies, which do not consider the diversity of the public, in terms of gender, livelihood and lack of family support.